1999
DOI: 10.1103/physrevb.60.874
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the composition and structure of cleaved and heat-treated icosahedral Al-Pd-Mn quasicrystal surfaces

Abstract: We investigated the changes in composition and structure induced by heat treatment of cleaved fivefold icosahedral Al-Pd-Mn quasicrystal surfaces by scanning electron microscopy and calibrated Auger electron spectroscopy. With increasing temperature we observed five different composition ranges of the surface coupled with distinct changes in the surface morphology. The changes in composition can be explained by successive evaporation and diffusion processes occurring with increasing temperatures. First, Mn eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…We note that the decrease in Mn at the fracture surface of the icosahedral phase after annealing has been reported previously, based upon Auger electron spectroscopy. 54 The deficiency in Mn at the surface of i-Al-Pd-Mn prepared by sputter annealing has also been reported from earlier observations by low energy in scattering, 55 and surface x-ray diffraction. 56 Nothing is known about the structures of the topmost layers in Ј or Al 6 Mn, nor do we know whether an enhanced DOS will be observed for the fractured surfaces of these materials.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We note that the decrease in Mn at the fracture surface of the icosahedral phase after annealing has been reported previously, based upon Auger electron spectroscopy. 54 The deficiency in Mn at the surface of i-Al-Pd-Mn prepared by sputter annealing has also been reported from earlier observations by low energy in scattering, 55 and surface x-ray diffraction. 56 Nothing is known about the structures of the topmost layers in Ј or Al 6 Mn, nor do we know whether an enhanced DOS will be observed for the fractured surfaces of these materials.…”
Section: Discussionsupporting
confidence: 64%
“…Published analysis of the fractured surface by STM revealed that over at least some of the surface, the cluster-subcluster structure evolves upon annealing toward a terrace-step topography. 10 In terms of electronic structure, the clusters are treated as spherical potential wells, each containing a magic number of electrons, corresponding to the exact filling of the electronic shells of the hierarchy of wells. The DOS is described as the superposition of the bonded states of the successive hierarchy of clusters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The one-dimensional height modulation of the structure yielded quasiperiodically ordered rows as observed by STM. 29,30 There are similarities between the two systems in that Fibonacci sequences and the golden ratio are identified in both. 20,30 The difference between the two structures is that one is grown on a periodic substrate and one is grown on a quasicrystal substrate; thus the Ag film develops a quasicrystalline structure in response to the periodic potential of the GaAs, and while the Cu forms a structure in response to the aperiodic potential of the quasicrystal, and is therefore "pseudomorphic."…”
Section: B Comparison With Ag/ Gaas"110…mentioning
confidence: 96%
“…[9][10][11][12][13][14][15][16][17] Annealing the sputtered surface at appropriate temperature routinely generates a stepterrace surface structure. In STM studies, an ultimate goal is to obtain high-resolution images displaying the fine structure ͑at the best, the direct images of the atomic arrangements͒ on these flat terraces, and to relate the surface structure to the atomic structure of a bulk model.…”
mentioning
confidence: 99%